Language Variations of Adolescents on Tiktok Social Media - Sulistiyarini, Siti; Prasetyo, Gilang Tegar (Universitas Tidar, 2024)
The use of language on social media which tends to adjust its pronunciation has given rise to a phenomenon called ecrononciation. This phenomenon has been happening in Indonesia for a long time, especially among teenagers. This causes the emergence of new language variations that displace old language variations over time. Therefore, this research aims to describe the differences in language variations of teenagers on social media, the function of language variations used by teenagers on social media, and the background that causes language variations of teenagers on social media. The method used in this research is a qualitative descriptive method. Data collection was carried out through listening and note-taking techniques sourced from videos uploaded by one of the TikTok social media user accounts. The data used in this research are oral statements accompanied by written transcripts uploaded by the account. The data that has been collected is identified and analyzed using the matching method based on the theory of language variation in sociolinguistic studies. Based on the results and discussion in this research, it was found that there are forms of adolescent language variation in the form of new forms, the emotive function of adolescent language variations on social media, and the background of adolescent language variations from time to time is influenced by speech situations and age factors.